2006
DOI: 10.1073/pnas.0509650103
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of centromere inactivation resulting in stable dicentric chromosomes of maize

Abstract: Somatic chromosome spreads from maize (Zea mays L.) plants containing B-A translocation chromosomes undergoing the chromosome type breakage-fusion-bridge cycle were examined by FISH. The size and type of extra chromosomes varied among cells of the same individual. A collection of minichromosomes derived from the chromosome type breakage-fusion-bridge cycle was examined for the presence of stable dicentric chromosomes. Six of 23 chromosomes in the collection contained two regions with DNA sequences typical of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
270
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 310 publications
(280 citation statements)
references
References 23 publications
7
270
0
3
Order By: Relevance
“…However, such chromosomes should be stable if only one centromere remains active (30), or if the centromeres in the dicentric chromosome are physically close and coordinate their movement to one or the other pole (31). Inactivation of redundant centromeres have been found in maize and other grasses (30,32,33), and although the details underlying the inactivation are not clear yet, several recent studies have suggested that plant centromere function is an epigenetic process (30,(32)(33)(34). The molecular details of such an epigenetic loss, and whether it involves dominance of one centromere over another (as seen for instance with nucleoli in some nascent polyploids; ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, such chromosomes should be stable if only one centromere remains active (30), or if the centromeres in the dicentric chromosome are physically close and coordinate their movement to one or the other pole (31). Inactivation of redundant centromeres have been found in maize and other grasses (30,32,33), and although the details underlying the inactivation are not clear yet, several recent studies have suggested that plant centromere function is an epigenetic process (30,(32)(33)(34). The molecular details of such an epigenetic loss, and whether it involves dominance of one centromere over another (as seen for instance with nucleoli in some nascent polyploids; ref.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure of engineered chromosome production does not rely on cloning centromere sequences from different plant species (38) and bypasses any complications of epigenetic components for centromere specification (39). Although the B chromosomes of various plant species (11) provide an attractive vehicle to produce engineered chromosomes, we present a proof of concept that minichromosomes can also be recovered from truncation events of A chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The centromere inactivation will ensure regular meiotic segregation of the fusion chromosome and can result in evolutionary fixed reduction of chromosome number. Several cases of inactivated ancestral centromeres as well as the emergence of neocentromeres (centromere repositioning) were reported in mammalian species (e.g., Ferreri et al, 2005;Ventura et al, 2007), but only a few examples of centromere inactivation (and reactivation; F. ) in plants, including dicentric chromosomes of Trititiceae (Sears and Camara, 1952;Luo et al, 2009), maize (Zea mays) B chromosomes (F. Han et al, 2006, and potentially also chromosomes of two cucurbit species (Y. . Except for the heterochromatic knob on chromosome SN3 corresponding to the AK5 centromere, no heterochromatin was observed at sites of the other 17 presumably inactivated centromeres.…”
Section: Species-specific Dysploidy Following the Wgdmentioning
confidence: 99%